Settlement of Workers’ Entitlements To Other Wage Components In The Event of Corporate Bankruptcy - Mochamad Ilham; Budi Santoso; Sugeng Santoso PN (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This thesis discusses the rights of workers in bankruptcy situations which have been regulated in the Manpower Law and the Bankruptcy Law, but their implementation still faces obstacles, especially related to the priority order of payments when compared to other creditors. Constitutional Court Decision Number 67/PUU-XI/2013 confirms that the obligation to pay wages to workers must take priority over all other types of creditors, including separatist creditors. This study aims to answer two problem formulations: (1) Are workers who experience termination of employment (PHK) due to the company going bankrupt in their position as preferred creditors entitled to other wages that have not been paid? and (2) How is the mechanism for payment of workers' rights to other wages that have not been paid compared to other creditors in the bankruptcy process. The research method used is normative juridical with a statutory, conceptual, and comparative approach. The results of the study show that workers who experience termination of employment (PHK) due to the company going bankrupt have the position of preferred creditors as regulated in Article 95 paragraph (4) of the Manpower Law and Article 39 paragraph (2) of Law Number 37 of 2004 concerning Bankruptcy and PKPU. This position gives priority rights to workers for payment of wages, including other wages that have not been paid. Thus, workers are entitled to other wages even though the company is in a state of bankruptcy, as long as it is recognized in the list of receivables. In the bankruptcy process, the mechanism for payment of workers' rights takes priority over concurrent creditors, but does not necessarily exclude separatist creditors (holders of property security rights). The order of payment begins with the settlement of bankruptcy costs, then workers' rights, only after that the remaining bankruptcy assets are used to pay separatist and concurrent creditors. With this mechanism, workers obtain legal protection for their wage rights, although in practice there are often obstacles due to the limited value of the available bankruptcy assets.